From Ruins to Resin: A Curator’s Fight to Save Ukrainian Heritage - Jacobsen, Scott Douglas (International Policy Digest, 2025)
Ukrainian curator Tetyana Fiks discusses how the War Fragments Museum preserves the human stories of war through art, using resin-encased artifacts to protect and share Ukraine’s cultural memory with the world.
Ukraine